Costs of flying units in Air Force active and reserve components - Robbert, Albert A., 1944- (Technical report (Rand Corporation) ;, 2013)
The relative costs of operating and supporting Air Force active- and reserve-component units are an important consideration in programming the mix of forces for various missions. Unfortunately, there are no generally accepted or well-documented methodologies for compiling the costs and output measures to be included in these comparisons. This report describes the development of one such methodology and applies it to an exploration of force mix alternatives in several weapon systems. Using data from the Air Force Total Ownership Cost decision support system from fiscal years 2006 through 2010, the author estimates the cost of operating the C-130 tactical airlifter, KC-135 aerial refueler, and F-16 multirole fighter fleets in Air Force active and reserve components. The author highlights the ways in which cost considerations favor the active and reserve components differently and discusses how this can help determine a cost-minimizing active/reserve mix.